PENGARUH PENGETAHUAN PERPAJAKAN DAN LAYANAN OTORITAS PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG DIMODERASI OLEH RELIGIUSITAS - Supartini, Supartini; Barokah, Siti (Media Akuntansi Perpajakan, 2018)
Abstract                The awareness of taxpayers in Indonesia to carry out their tax obligations is felt to be very minimal in terms of compliance and self-awareness, they pay taxes due to forced elements and this is due to many influencing factors including frequent changes in regulations, lack of socialization, complexity in calculations, payments and reporting is also due to the services of the tax authorities which make taxpayers feel comfortable and more open in resolving the obstacles they face in taxation. The purpose of this study was to examine the relationship between tax knowledge and tax authority services and investigate the moderating effects of religiosity on individual taxpayer compliance. The population in this study are individual taxpayers who have worked or have income. Samples were taken using convenience sampling and obtained 104 respondents.                The results of the study show that: 1) Knowledge of taxation has a positive and significant effect on individual taxpayer compliance. 2) Tax authority services do not affect individual taxpayer compliance. 3) Religiosity does not affect individual taxpayer compliance. 4) Religiosity cannot moderate the effect of tax knowledge on individual taxpayer compliance. 5) Religiosity cannot moderate the effect of tax authority services on individual taxpayer compliance.Keywords: knowledge of taxation, tax authority services, taxpayer compliance, religiosity.